Prevalence of idiopathic epilepsy and structural epilepsy in 74 Boxer dogs in a referral hospital - Loncarica, Tina; Balducci, Federica; Bernardini, Marco (Frontiers in Veterinary Science, 2022)
The prevalence of idiopathic epilepsy and structural epilepsy in Boxer dogs is unknown. The aim of this retrospective study was to evaluate the prevalence of structural and idiopathic epilepsy in the Boxer population. A total of 74 Boxer dogs were included in the study from the database of one referral hospital and the following were recorded: signalment, history, clinical findings and results of advanced diagnostic imaging. Five dogs (6.8%) were diagnosed with idiopathic epilepsy, of which one was in the <6 months age group, three were in the 6-72 months age group and one was in the >72 months age group. Sixty-nine dogs (93.2%) were diagnosed with structural epilepsy. Sixty-six had a suspected intracranial neoplasia: eight were in the 6-72 months age group and represent 66.7% of the dogs in that age group. The other fifty-eight were in the >72months age group and represent 96.7% of the dogs in that age group. In our Boxer population, 81.8% of the patients had a suspected intra-axial tumor and 22.7% of dogs with an intracranial pathology nevertheless had a normal neurological examination. In conclusion, in the majority of boxer patients the cause of epilepsy is a suspected intracranial neoplasia regardless of the age at presentation. Considering the finding in this study of a low prevalence of presumed idiopathic epilepsy in the Boxer breed, it is recommended that patients who satisfy Tier I confidence level of the “International Veterinary Epilepsy Task Force” (IVETF) also undergo an MRI study of the brain.